1969
DOI: 10.1103/physrev.188.2077
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry Parameter and Branching Ratio ofΣ+pγ

Abstract: E 7 interval over which the fit is carried out, the cross sections p7r + 7r~ir 0 , whereA N exposure of 1.3X10 6 pictures in the Berkeley 25-in. hydrogen bubble chamber yielded about 57 000 events of the typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Introducing weak breaking of SU(3) symmetry one expects to observe small decay asymmetries. In contrast to this, a large negative decay asymmetry in the weak radiative decay Σ + → pγ was first measured by Gershwin et al [4] and later confirmed [5]. To address this observation, models were developed which tried to obtain large decay asymmetries in spite of weak SU(3) breaking.…”
Section: Introductionmentioning
confidence: 96%
“…Introducing weak breaking of SU(3) symmetry one expects to observe small decay asymmetries. In contrast to this, a large negative decay asymmetry in the weak radiative decay Σ + → pγ was first measured by Gershwin et al [4] and later confirmed [5]. To address this observation, models were developed which tried to obtain large decay asymmetries in spite of weak SU(3) breaking.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, the number of py events detected in both experiments was very small (61 [2] and 46 [3], respectively).…”
Section: S7 Petersburg Nuclear Physics Institute Gatchina Russia ^mentioning
confidence: 81%
“…Polarization experiments with baryons often show results that are substantially different from the ones obtained in theoretical calculations made beforehand. It is possible to point to such researches as examples: the deep inelastic scattering of longitudinally polarized muons by longitudinally polarized protons [1]; the production of the hyperons Σ 0 [2] and Ξ + [3] by polarized protons on Be nuclei; the decays of polarized hyperons Σ + → pγ [4]. It is especially worth noting a substantial discrepancy in the values of the ratio of the electric G E and magnetic G M form factors of the proton obtained in two series of experiments on elastic electron-proton scattering staged at Jefferson Laboratory.…”
Section: Introductionmentioning
confidence: 99%